Zinc Finger Protein CTCF Regulates Extracellular Matrix (ECM)-Related Gene Expression Associated With the Wnt Signaling Pathway in Gastric Cancer - Liu, Chenbin; Deng, Linyi; Lin, Jinrong; Zhang, Jianjun; Huang, Shu; Zhao, Jinglin; Jin, Peipei; Xu, Peiqing; Ni, Peihua; Xu, Dakang; Ying, Le; Hu, Yiqun (Frontiers in Oncology, 2021)
Gastric cancer (GC), a leading cause of cancer-related death, is a heterogeneous disease. We aim to describe clinically relevant molecular classifications of GC that incorporates the heterogeneity and provides useful clinical information. We combined different gene expression datasets and filtered a 7-gene signature that related to the extracellular matrix (ECM), which also showed significant prognostic value in GC patients. Interestingly, putative CCCTC-binding factor (CTCF) regulatory elements were identified within the promoters of these ECM-related genes and were confirmed by chromatin immunoprecipitation sequencing (ChIP-Seq). CTCF binding sites also overlapped with histone activation markers, which indicated direct regulation. In addition, the ECM-related gene signature was highly enriched for CTCF transcription factor, which was also correlated with the Wnt signaling pathway. A comparison of human GC cell lines with high or low expression of ECM-related genes revealed different levels of tumor aggressiveness, suggesting the cancer development-promoting functions of ECM-related genes. Furthermore, the silencing of CTCF led to the reduction of COL1A1 and COL3A1 mRNA level. Silencing WNT5A and CTCF or silencing WNT3A and CTCF markedly inhibited cell migration ability in a metastatic GC cell line. Collectively, we show that the zinc finger protein CTCF regulates ECM-related gene signature, which is also linked with Wnt signaling pathway. This could provide a novel insight for survival prediction among GC patients.